Building Magic - Davies, Owen. author. aut Link
VII, 179 p.
Keywords: This book redresses popular interpretations of concealed objects, enigmatically discovered within the fabric of post-medieval buildings. A wide variety of objects have been found up chimneybreasts, bricked up in walls, and concealed within recesses: old shoes, mummified cats, horse skulls, pierced hearts, to name only some. The most common approach to these finds is to apply a one-size-fits-all analysis and label them survivals and apotropaic (evil-averting) devices. This book reconsiders such interpretations, exploring the invention and reinvention of traditions regarding building magic. The title Building Magic therefore refers to more than practices that alter the fabric of buildings, but also to processes of building magic into our interpretations of the enigmatic material evidence and into our engagements with the buildings we inhabit and frequent.